The OPTIMALISASI PEMBINAAN WILAYAH DALAM PENCEGAHAN DAN PENANGGULANGAN HIPERTENS - Darwis, Darwis; Patroni, Rini; Ismiati; Sumaryono, Dino (LPPM UPN Veteran Jakarta, 2024)
Kelurahan Anggut Atas has been determined to have a fostered area for Tri Dharma of Higher Education activities. The Department of Health Promotion, as a form of activity, among others, activities in the Real Work Practice Village Laboratory (PKNLD) were carried out January 30 to March 11, 2023. Activities begin with the Family Approach (PIS-PK) and Self-Inspection Survey (SMD) to determine health problems. The priority problem of Non-Communicable Diseases (PTM) was determined, namely Hypertension Disease which is related to lifestyle and many suffer from the Elderly. The implementation of case finding, management and prevention of hypertension patients in the fostered area of the Health Promotion Study Program in Kelurahan Anggurt Atas, The Result Every Friday for 4 weeks in the courtyard of the At Taqwa Mosque, February 2023 exercise activities are carried out together with blood pressure measurements for 35 residents, it is found that 10 residents have hypertension with an average BP of 145/90 mmHg and 25 residents are normal, February 24 2023 exercise activities and BP measurements blood totaling 38 people, there were 22 people with hypertension and poetryberian juce melon. February 27, 2023, door to door visits to families of 10 families and distribution of celery seeds to families of 10 people suffering from hypertension who were met door to door, blood pressure checks with average results of 130/100 mmHg and education. March 3, 2023 and 10 In March 2023, 42 and 45 residents took part in exercise together with education on hypertension, lifestyle and self-care and blood pressure checks. This activity was successful and received support from the village health center, neighborhood associations, neighborhood associations and cadres as seen by the enthusiasm of the community to participate in the activity. It is hoped that routine and integrated activities for the prevention and control of hypertension and other NCDs can be used as an example for other regions. Keywords: Prevention, management, hypertension